Dental Caries in Relation to Type of Disability: A Cross-sectional Study of Disabled Children in Tehran, Iran: Dental Caries and Disability in Tehran's Children - Ghorbani, Zahra; Fathi, Homa; Bassam, Alsheakhly; Ghsemi, Hadi; kazemi, Alireza; Namdari, Mahshid (Journal of Dental School, 2024)
Objectives Literature has reported high caries prevalence and unmet dental treatment needs among disabled individuals. This study was carried out to assess the oral health condition of disabled students in relation to age, gender, and type of disability in Tehran, Iran. Methods The study involved 1,170 disabled students aged 6 to 20 years, each with one or more of the following disabilities: physical retardation (PR), hearing impairment (HI), visual impairment (VI), mental retardation (MR), and autism spectrum disorder (ASD). The mean decayed, missing, and filled teeth index was used as an oral health indicator (dmft for children aged 6-12 years, and DMFT for children older than 9 years). Mann-Whitney and Kruskal-Wallis tests at significant level of 0.05 were conducted for comparisons. Results Mental retardation (MR) was the most prevalent disability (59.4%). The decayed component constituted the largest part of the mean dmft (82%) and DMFT (75%) indices in all age groups. Girls had significantly higher DMFT scores compared to boys (P < 0.001). Among the different disabilities, children with HI had the highest dmft score (mean ± SD = 2.17 ± 2.86), while those with MR had the highest DMFT score (mean ± SD = 3.76 ± 3.83). Additionally, the caries-free ratio was significantly higher among VI students in the 9-12 years (40.5%) and older than 13 years (38.8%) age groups. Conclusion The high prevalence of untreated dental caries, particularly among those with HI and MR, points to significant unmet treatment needs and emphasizes the importance of regular dental check-ups and access to dental care. These results underscore the critical need for improved oral health services and preventive programs tailored to the specific needs of disabled students.